Capital flows, capital controls and currency crisis: The case of Brazil in the nineties - Márcio Gomes Pinto Garcia; Marcus Vinicius Ferrero Valpassos (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1998)
The resumption of capital flows to developing countries in the nineties is intertwined in the Brazilian case with the attempts to achieve inflation stabilization. A very restrictive monetary policy has offered probably the world's highest yield to fixed income investments. In the context of favorable external factors to capital flows, the huge interest rate differential caused massive short term capital inflows to Brazil. After 1995, foreign direct investment, mainly associated with the privatization process, has became more important as a source of foreign capital. During the first period, the magnitude of those flows exacerbated two main macroeconomic problems: an increase in the quasi-fiscal deficit due to the interest payments on the debt used to sterilize the inflows, and, after the Real Plan, also the overvaluation of the currency. The restrictions to capital inflows are described and analyzed, as well as the main financial engineering strategies used to circumvent the restrictions. Given the advanced stage of domestic financial markets - including a powerful derivatives market- the restrictions imposed have not been fully effective in preventing the inflows of short term foreign capital to invest in the high-yield-public debt, but they probably had a temporary effect. Given the small progress achieved so far in the fiscal side of the reforms, it is also doubtful that the capital inflows' restrictions have been effective in a broader sense, that of allowing the government to buy time to implement the essential structural reforms. By reducing the urgency of the politically costly structural reforms aimed at increasing domestic savings, capital inflows have detrimental incentive effects on the government's resolve to push forward the stabilization plan, as shown by the lack of commitment in carrying out the fiscal package promised during the Asian crisis. If the external finance package is successful in deterring the current daily losses of foreign reserves and in regaining the market's confidence, it remains to be seen if the current crisis was strong enough to make the newly reelected Brazilian government live up to its renewed promise of fiscal austerity.
Keywords: 330